The Effect of Jigsaw Learning Strategies on the Metacognition of Tenth Grade Students on Fungi Material: A Case of MA Baitussalam - Ningsih, Sulis Tia; Ulfa, Syarifah Widya (Jurnal Pendidikan MIPA, 2022)
This study aims to find out how the influence of Jigsaw learning strategies on students' metacognition development. This study uses a quantitative method by distributing questionnaires to students in both classes, namely control and experiment. The population in this study was 56 students. From this study, it was found that the use of the Jigsaw type learning model in MA could provide an increase in students' metacognition. This is indicated by the average number of students' metacognition in the treatment class is higher than in the control class, namely 7,643 for the treatment group and 6,286 for the control group. The treatment class is smaller than the control class if the standard deviation is the benchmark, with 0.1174 for the treatment class and 0.1442 for the control class, which means that the jigsaw type cooperative learning model has an effect on improving students' metacognition. . Keywords: cooperative learning, jigsaw, metacognition.  DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1464-14710